Design of A Green Hydrogen System Powered by Solar Power Plants in Lombok - Parman, Parman (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2024)
Hydrogen is a carbon-free energy source with significant potential as a sustainable energy carrier for the future. Green hydrogen production through renewable energy sources, such as Solar Power Plants (PLTS), offers high potential for decarbonizing various sectors and addressing climate change challenges. This research aims to design a hydrogen production system integrated with a PLTS system in Lombok. Using MATLAB Simulink, a model is utilized to simulate the potential for green hydrogen production using an off-grid PLTS. The study includes an analysis of the PLTS system design, an electrolyzer model, and an energy storage system. Solar radiation data from 2023 is used as the basis for the simulation. The simulation results show that a PLTS with a capacity of 2.33 MWp and a Proton Exchange Membrane (PEM) electrolyzer system with a power of 2 MW can produce 121,391 kg of hydrogen per year.